TECHNICAL INSPECTION OF THE STRUCTURE AND DEVELOPMENT OF THE STRUCTURE OF FRAMES WITH COLD-ROLLED THIN-WALLED PROFILES (Collection of scientific works «Modern structures of metal and wood», 2021)
Cold rolled steel structures have been known since the mid-19th century in the United States and Great Britain.  Despite the advances in the development of cold-rolled structures, the level of their use was lower  than  that  of  hot-rolled  structures.  A  significant  factor  that  influenced  this  imbalance  in application was the fact that there were no regulations. Into different countries of the world have their own  national  regulations  for  the  calculation  of  cold-rolled  steel  structures,  which  have  many controversies. In the European group includes the norms of the countries of the European Union, Great Britain, Hong Kong, Ukraine, Belarus, Kazakhstan; American group - the United States of America, Canada, Mexico, Australia, New Zealand, Brazil, Chile, Egypt. The regulations of such large countries as China, India and Russia have their own characteristics. The article presents the results of a technical survey of the load-bearing structures of the canopy. The survey was carried out to determine the bearing capacity of the roof load-bearing structures in relation to the location of the solar panels on the roof of the building.  The construction of buildings and their structural parts from light steel thin-walled structures (profiles) is carried out in the form of light frames, the frames of which are successively connected into spatial systems. A new lightweight roof covering made of profiled sheet and a frame structure made of cold-rolled P-profile and C-profile elements for roofing and installation of solar panels are proposed.  Such  a  coating  is  the  most  industrialized,  easily  and  quickly  erected.  The  analysis  of constructive options for the effective placement of the profile of cold-rolled elements and joints of the frame and reinforced concrete run of the coating is carried out. The design of the frame was carried out in the software package " Лира САПР 2013" . The  results  of  the  work  carried  out  served  to  draw  up  recommendations  for  restoring  the properties of the load-bearing structures of the  canopy, the development of design estimates and implementations into construction practice during the reconstruction of the canopy.